MANUSIA PERTAMA DALAM PERSPEKTIF AL-QURAN - Nasution, Abd Halim (Tazkiya: Jurnal Pendidikan Islam, 2020)
There are some hypotheses tried to describe the origin of human, but there is no the certainty of how the homo erectus was born. The only sources which is agreed by expert that homo sapiens came from homo erectus. In the Islamic belief, the humans are created particularly to serve Allah SWT and had role as khalifah in the world. The creating of basyar (the first human) is from clay which is derived from altered black mud, then Allah make his ancestry from sperm-drop. The creating of first human is from the process till perfection (tasawiyyah), not directly to be perfect as a human. It is understood from the word of tasawwiyah from sawwa means make perfection, the performing of something from the part until perfection. The process of creating the first human is said in the holy Quran with the verb like kun fayakun, nasy’, nabat and sawar. Adam as the Abu al-Basyr (the father of human) is the first human not as the successor or substitute of the previous human explicitly and implicitly, but as the first generation which is created by Allah as khalifah in the world. The keywords: human, perspective and Quran